قصیدة "أراك عصي الدمع" لأبي فراس الحمداني مقاربة أسلوبیة نفسیة (Journal of the College of Education for Women, 2019)
This work falls into a two sections, and a conclusion. The first sectionpresents the problem of the study, its importance, methodology, and review ofliterature. The poem of “?araaka ؟asiyya dam؟’ (I Found You a Tear-Refractory)for Abi-Firaas Al-Hamdani, represents the main code of the study through whichthe two researchers try to approach the stylistic and psychological studies. Toaccomplish such an approach, they try to link between a group of the poet’spsychological characteristics and another group of prominent stylistic phenomenafound in the poem. The conclusion contains the main results the two researchershave arrived at.